2015
DOI: 10.1589/jpts.27.3299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ankle proprioceptive training on static body balance

Abstract: [Purpose] This study aimed to investigate the effect of ankle proprioceptive training on static body balance. [Subjects and Methods] In this randomized-controlled, single-blind study, 59 university students (35 females, 24 males) were randomized into study (n=29) and control (n=30) groups. The study group received a foot and ankle proprioceptive exercise program including stretching, strengthening (plantar and dorsi-flexors, invertor and evertor muscles), and balance board exercises, each with 10 repetitions p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Among healthy non-athlete subjects, Chong et al 24 reported an improvement in balance control ability following an ankle proprioception training programme, although their results revealed that a training programme that controlled general balance did not specifically target ankle proprioception. Karakaya et al 25 reported that ankle proprioceptive training had positive effects on static body balance parameters in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Among healthy non-athlete subjects, Chong et al 24 reported an improvement in balance control ability following an ankle proprioception training programme, although their results revealed that a training programme that controlled general balance did not specifically target ankle proprioception. Karakaya et al 25 reported that ankle proprioceptive training had positive effects on static body balance parameters in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by weakness of dorsiflexors (e.g., tibialis anterior, extensor halluces longus, and extensor digitorum longus) and stiffness of plantarflexors (e.g., gastrocnemius, soleus, tibialis posterior, flexor halluces longus, and flexor digitorum longus) following stroke [4]. Ankles are located close to the body's base of support and assist in controlling balance [5]. Limited ankle ROM in most stroke survivors impairs balance control, which is a major risk factor for falls [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by other authors confirm that even a short-term period of balancing exercises may benefit body stability. Karakaya et al [25] observed significant changes in postural stability following two weeks of proprioceptive training with persons not engaged in sports. Vando et al [26] applied one week of coordination training in 10-yearold karate fighters, noting significant changes in body stability, as measured on a stable platform.…”
Section: Discussionmentioning
confidence: 99%